2013
DOI: 10.4028/www.scientific.net/amm.471.138
|View full text |Cite
|
Sign up to set email alerts
|

A Literature Analysis on Acoustical Environment in Green Building Design Strategies

Abstract: Acoustic quality is important in ensuring a healthy and workable working environment. One of green buildings main objective is to reduce the building impact on human health and performance. This was emphasized in most green building rating system under its requirement for Indoor Environmental Quality (IEQ). IEQ highlights the four main points for achieving an improved indoor environment: indoor air quality, acoustics, visual comfort (lighting) and thermal comfort. Although acoustics was mentioned in the IEQ cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…According to Hodgson, 5 LEED basically disregard the acoustical environment requirement and this has unfortunately made it very unlikely for architects and designers to consider acoustics as an important aspect of green buildings. 17,18 This was confirmed by Lee and Guerin 19 in their study on occupants' satisfaction and performance in LEED-certified buildings. The study explained that LEED IEQ requirements address only on issues related to mechanical aspects of the indoor environment such as indoor air quality (IAQ), low emitting materials, indoor chemical and pollutant source control, controllability of systems, thermal comfort and daylighting systems.…”
Section: Introductionsupporting
confidence: 72%
“…According to Hodgson, 5 LEED basically disregard the acoustical environment requirement and this has unfortunately made it very unlikely for architects and designers to consider acoustics as an important aspect of green buildings. 17,18 This was confirmed by Lee and Guerin 19 in their study on occupants' satisfaction and performance in LEED-certified buildings. The study explained that LEED IEQ requirements address only on issues related to mechanical aspects of the indoor environment such as indoor air quality (IAQ), low emitting materials, indoor chemical and pollutant source control, controllability of systems, thermal comfort and daylighting systems.…”
Section: Introductionsupporting
confidence: 72%
“…Most researchers believe the certified GBs perform better than conventional buildings in terms of IEQ and energy use [148][149][150]. There are four main variables highlighted in GBRSs to improve IEQ: thermal quality, acoustic quality, visual quality, and indoor air quality (IAQ) [151][152][153]. Lin et al found the satisfaction of users in certified GBs is higher than conventional buildings in terms of thermal comfort and IAQ [154].…”
Section: Technologies Applicationmentioning
confidence: 99%
“…Generally located at the center of the building, the atrium can be acted as a key circulation and transition space to proceed to other spaces (Wood & Salib, 2013;Pitts, 2013;Passe & Battaglia, 2015). It also gives an impression of large volume and has the potential to provide good air circulation and light penetration towards indoor comfort within the space (Jalil et al, 2014;Bai et al, 2015;Moosavi et al, 2014;Moosavi et al, 2015). Nowadays, the atrium is widely used in residential, commercial, and institutional buildings and not only acts as protection from the climate conditions but also creates a significant visual effect on the existing space.…”
Section: Introductionmentioning
confidence: 99%